Revolutionizing MSMEs: The Impact of Mobile Payment Readiness through TOE Framework - Aprisca, Devtania Putri; Aligarh, Frank (Universitas Muhammadiyah Magelang, 2024)
This study seeks to examine the influence of the Technology, Organization, and Environment (TOE) Framework on the adoption of mobile payments and its consequential impact on firm performance. Employing a purposive sampling technique, data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). Questionnaires served as the primary data collection method and were distributed among 202 micro, small, and medium enterprises (MSMEs) in Surakarta City. The results underscore that TOE Framework factors, encompassing relative advantage, compatibility, innovativeness, and competitive pressure, wield a positive and significant influence on the adoption of mobile payments. Nevertheless, mobile payment knowledge and external support were found to have no substantial effect on mobile payment adoption. Notably, the study establishes a positive and significant relationship between mobile payment adoption and firm performance. These findings contribute valuable insights for businesses aiming to leverage mobile payment technologies to enhance overall performance in the contemporary business landscape.